Knowledge on occupational health hazard and safety practices among the municipal solid waste handler - Marahatta, Sujan B; Katuwl, D; Adhikari, S; Rijal, K (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: All over the world nearly 860,000 people are injured every day and 2.3 million deaths occur annually due to occupational accidents and work-related diseases.There are limited studies that specifically determine the knowledge of waste handlers on occupational health problems and associated factors of occupational health problems and injuries in waste handlersin context of Nepal. Therefore, this studyaimed to assess the knowledge of waste handlers on occupational health and safety practices and its association with utilization of PPEs along with the condition of occupational health problems and injuries and factors associated with them among the waste handlers of Kathmandu Metropolitan City.Methods: A descriptive cross-sectional survey was conducted among selected 355 solid waste collectors by using semi-structured questionnaire and observation checklist, which was completed from March 2016 to May 2016. The data was entered into SPSS 20 version for analysis and a chi-square test was performed to see the presence of the association between the dependent and selected independent variables.Results: Among total respondents (355) surveyed 51.5% had got knowledge on occupational health hazard, 16.1 %  had got the knowledge to prevent from work-related health risks, 29% had got knowledge about PPEs and  31.5% had got knowledge about PPEs utilization. About 45.8% of the study participants had practices of the utilization of PPEs. Majority of the respondents i.e. 63.7% reported that they were suffering from occupational health problems. The evidence of the occupational health injuries was found to be low i.e. 25.4%. Similarly, variables which had significant influence on the occupational health problems were knowledge on occupational health hazard (p=0.016), work experience (p=0.021), health checkup (p=0.042) and for the occupational health injuries were monthly income(p=0.036), knowledge to prevent from health risk (p=0.001), gender (p=0.02), and knowledge of occupational health hazard (p=0.011), work experience (p= 0.025), work type (p=0.001), knowledge on PPEs ( p=0.034) and knowledge on work-related health risks (p= 0.027).Conclusion: Based on this study, its recommended to improve occupational health and safety practices. Awareness programs need to be focused to increase the knowledge on Occupational health hazards and safety practices to improve the utilization of PPEs..Journal of Manmohan Memorial Institute of Health SciencesVol. 3, No. 1, 2017, page: 56-72